Ideal antenatal care-does it exist? - Singh, Sanjay; Biswas, Manash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Antenatal care is systematic supervision of a pregnant mother and its objective is to ensure a normal pregnancy with delivery of a healthy baby from a healthy mother. It is quite effective in reduction of maternal and perinatal mortality and morbidity. Varied antenatal care protocols exist in the literature and all aim towards the same goal. This review endeavours to find out a protocol that is ideal and that suits every pregnant woman, every institute and every country in the world. The review was carried out in the period of 1900-2015 by searching in pub med, embase, scopus, google scholar, web of sciences using relevant key words. Reports, articles, fact sheets and official publications of World health Organization (WHO), Ministry of health and family welfare-government of India and various other countries were also reviewed. The review suggests that no such ideal protocol appears to exist that suits the requirement of every pregnant woman / country. However, it is possible to make and implement a near ideal protocol which is evidence based and is logistically and economically viable, for an optimal pregnancy outcome.